Impact of the Type of Dialysis Membranes on the Circulating Concentration of Markers of Vitamin D Metabolism. Issue 2 (February 2017) - Cavalier, Etienne; Torres, Pablo U.; Dubois, Bernard E.; Smelten, Nicole; Pottel, Hans; Krzesinski, Jean-Marie; Delanaye, Pierre
Introduction: Kidney Disease Improving Global Outcomes (KDIGO) guidelines recommend vitamin D supplementation in hemodialyzed patients to monitor 25(OH)-vitamin D 25(OH)D levels. However, patient-to-patient inconsistency can be observed in response to the treatment. In this study, we aimed to evaluate the impact of the dialysis membrane on 25(OH)D, albumin (Alb) and vitamin D-binding protein (VDBP), the major players of vitamin D transport and storage. Material and Methods: Alb (Cobas), VDBP (R&D) and 25(OH)D (liquid chromatography-tandem mass spectrometry) were measured in 75 patients before and after a 4-hour dialysis session. Ten dialysis membranes were used: FX10, FX80, FX800, BK-2.1F, BG-2.1U, Rexeed 15 A, Rexeed 21 A, TS 1.8 SL and TS 2.1 SL manque la ELISIO 21H. Accordingly, 13 patients were dialyzed with membranes possessing high adsorption and high cut-off properties (BK), 17 with membranes possessing high adsorption but usual cut-off properties (BG) and all the remaining 45 patients with polysufone (PS) membranes with usual adsorptive and cut-off properties. Among these 45 patients treated with PS, we compared those treated by classical dialysis (HD) (n = 14) and hemodiafiltration (HDF) (n = 31). Results were corrected for total extracellular volume to take into consideration the hemoconcentration after dialysis Results: The 3 analytes showed a decreased concentration after the dialysis session. The decrease of ALB, VDBP and 25(OH)D was similar with the adsorptive (BG) and PS membranes. However, patients treated with adsorptive and high cut-off membrane (BK) presented a significantly higher decrease values of Alb (-9.6%[-15.1; -7.5]), of VDBP (-20.6%[-36.6; -17.2] and 25(OH)D (-17%[-27.3; -12.3]) compared to other membranes (BG and PS). When we limited our study to PS membranes, we did not observe any significant difference between the HD or HDF modalities in the decrease for any of the studied parameters. Conclusions: A significant loss of Alb, VDBP and 25(OH)D occurs after a dialysis session. This loss is significantly more important when patients are dialyzed with high adsorption and high cut-off dialysis membranes